Emotion Regulation in Workgroups: The Roles of Demographic Diversity and Relational Work Context. Issue 3 (8th May 2013) - Kim, Eugene; Bhave, Devasheesh P.; Glomb, Theresa M.
<x xml:space="preserve">Abstract</x> Drawing on the social identity perspective, we investigate the cross‐level relationship between demographic diversity in workgroups and emotion regulation. We propose that age, racial, and gender diversity in workgroups relate positively to emotion regulation because of demography‐related in‐group/out‐group dynamics. We also examine the moderating role of the relational work context, specifically task interdependence and social interaction, on the relationship between demographic diversity and emotion regulation. Results from a sample of 2, 072 employees in 274 workgroups indicate that working in a group with greater age diversity is positively related to an employee's emotion regulation. Results suggest the operation of the age diversity effect can be attributed primarily to younger employees when they are in workgroups with older coworkers. Results reveal asymmetric effects for racial diversity such that racial out‐group members engage in higher levels of emotion regulation than racial in‐group members when racial diversity is low, whereas racial in‐group members engage in higher levels of emotion regulation than racial out‐group members when racial diversity is high. Race effects also suggest a moderating effect of social interaction; specifically, social interaction weakens the relationship between racial diversity and emotion regulation. Gender effects are not significant.